Implementation of Fe ion irradiation and high-temperature target design at KAHIF for neutron damage simulation in fusion structural materials - Sangbeen Lee; Dae-Sik Chang; Kihyun Lee; Sung-Ryul Huh; Seunghyun Lee (Nuclear Engineering and Technology, 2025)
The development of radiation-resistant materials is critical for realizing future fusion energy. Ion beam irradiation facilities provide an efficient method for evaluating material performance, offering accelerated testing at higher Displacement Per Atom (DPA) rates compared to reactor-based neutron irradiation. The Korea Atomic Energy Research Institute Heavy Ion Irradiation Facility (KAHIF) is a dedicated accelerator system for such research on nuclear fusion and fission materials. This paper provides a comprehensive overview of the KAHIF system. KAHIF employs an 18 GHz Electron Cyclotron Resonance Ion Source (ECR-IS) and a 25.96 MHz Split Coaxial Radio Frequency Quadrupole (SC-RFQ) to accelerate various ions, including He, Ar, and Fe, to approximately 178 keV/u, with the potential for further acceleration up to 1.0 MeV/u using an Interdigit H-mode Drift Tube Linac (IH-DTL). We detail its current operational characteristics, research applications including DPA assessments, and recent developments such as Fe ion delivery using the Metal Ion Volatile Compound (MIVOC) method. Furthermore, the ongoing upgrade of the medium energy beam transport (MEBT) line to enhance experimental capabilities is presented. Through these capabilities and continuous improvements, KAHIF plays a crucial role in advancing materials science for future nuclear energy systems.